2004
DOI: 10.1038/nn1244
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine amplifies reward-related dopamine signals in striatum

Abstract: Reward-seeking behaviors depend critically on dopamine signaling--dopamine neurons encode reward-related information by switching from tonic to phasic (burst-like) activity. Using guinea pig brain slices, we show that nicotine, like cocaine and amphetamine, acts directly in striatum where it enhances dopamine release during phasic but not tonic activity. This amplification provides a mechanism for nicotine facilitation of reward-related dopamine signals, including responses to other primary reinforcers that go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

55
708
4
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 507 publications
(768 citation statements)
references
References 15 publications
55
708
4
1
Order By: Relevance
“…A bidirectional effect of nicotine on dopamine release has been demonstrated; i.e. when stimulating electrically at a low frequency (representing tonic release) nicotine decreased dopamine release, when stimulating at high frequency (representing phasic release) nicotine increased dopamine release [5,6]. Our study confirmed these findings of the effect of nicotine on stimulated dopamine release.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A bidirectional effect of nicotine on dopamine release has been demonstrated; i.e. when stimulating electrically at a low frequency (representing tonic release) nicotine decreased dopamine release, when stimulating at high frequency (representing phasic release) nicotine increased dopamine release [5,6]. Our study confirmed these findings of the effect of nicotine on stimulated dopamine release.…”
Section: Discussionsupporting
confidence: 87%
“…Most importantly we have shown for the first time that both inhibition (SCH-23390) and stimulation (SKF-38393) of the D1R profoundly attenuated the effect of nicotine on presynaptic activity. For many years it was believed that dopamine release from the ascending pathway was modulated by nicotine [2, 5,6]. However, this conclusion was made from studies based on stimulation without considering a possible contribution of the ChI-driven dopamine release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These contradictory findings might be explained by the more recent observation that used cyclic voltametry to obtain a better resolution of time-dependent effects of nicotine application on dopamine release. The data obtained using striatal [117] and nucleus accumbens [118] slices are identical: nicotine produces a decrease in dopamine release following a single electrical stimulation and an increase in release following a burst of five stimulations. These observations argue that both somatodendritic and nerve terminal nAChRs play important roles in modulating the release of dopamine from dopaminergic neurons.…”
mentioning
confidence: 75%
“…10 Nicotine addiction is a significant health problem, with smoking ranking as the primary cause of preventable death worldwide. Roughly 90% of the people who attempt to quit are unable to do so.…”
mentioning
confidence: 99%